Legal protection for doctors’ work safety in handling Covid-19 cases reviewed based on Saddu al-Dzari’ah - Rizka, Rizka; Junaidi, Muhammad; Lyandova, Vanka; Ab.Rahman, Rozanah (Faculty of Law, University of Muhammadiyah Malang, 2022)
Legal protection for doctor's work safety during the Covid 19 pandemic has not received optimal preventive action from the government with the data showing that the death of health workers in Indonesia accounts for the highest in Asia. This study aims to discuss the concept of legal protection for doctors' work safety in handling Covid-19 cases on the basis of Saddu al-Dzari'ah. The main data source for this study's juridical-normative methodology consisted of secondary data from written legal materials quantitatively examined to provide analytical descriptive data. Results show that legal protection for the safety of doctors in dealing with Covid-19 cases cannot be as required and correctly implemented in the legislation; in reality, the rights of doctors are still neglected and not fulfilled. The government's failure to take preventive measures to offer legal protection for doctors means that mafsadat (injury) in managing Covid-19 cases persists, which is also evidenced by the number of doctors who died from Covid-19. Our findings suggest the importance of having the concept of legal protection for doctors in handling Covid-19 cases based on Saddu al-Dzari'ah so that doctors get comprehensive protection.